Pengaruh Display Produk Dan Promosi Terhadap Keputusan Pembelian Konsumen Pada Buku Terbitan Mizan (Studi Kasus Toko Buku Gunung Agung BSD) - Prassetyo, Nuggraha; Hanny, Rissa (Media Ekonomi, 2021)
The purpose of this study was to determine how much influence the product display and promotion partially on consumer purchasing decisions on books published by Mizan at Gunung Agung BSD Tangerang bookstore and to find out how much influence the product displays and promotions simultaneously on consumer purchasing decisions on books published by Mizan at the Gunung Agung BSD Tangerang bookstore. This research is causality with quantitative approach. The population in this study is Mizan’s book customers at the Gunung Agung BSD bookstore Tangerang with convenience sampling technique obtained samples of 69 respondents. Data analysis techniques used in this study are: data quality tests including validity and reliability, the classic assumption test of normality, multicollinearity, heterocendatisity, regression analysis that is multiple regression, partial t, simultaneous F and coefficient of determination. The results of the study are as follows: (1) The results of first hypothesis that is no significant influence between product displays on consumer purchasing decisions, (2) The results of second hypothesis that is a positive and significant effect between promotions on decisions consumer purchases, and (3) The results of third hypothesis, namely product display and promotion together have a positive and significant effect on consumer purchasing decisions.